PEMBELAJARAN BUDAYA JEPANG MELALUI MEDIA DVD ERIN GA CHOSEN - Lispridona Diner (Universitas Diponegoro, 2013)
Abstract A course of study japanese state university education director of semarang there is a course called nihonjijo. Formerly learning nihonjijo using media power point. After evaluated, the result of learning a student of course, only acquiring knowledge without understand japanese culture. The formulation of problems in this research is “ whether the use of the media dvd erin ga chosen can improve understanding learner japanese with the culture japan?” The method is applicable in a method of direct observation. The technique of the collection of data used is a technique poll. Poll propagated to students semester 1 who follows college course nihonjijo some 58 college students study program education Japanese State University Semarang force 2013. And, based on the results of the discussion then can be concluded that cultural learning Japanese through access to a dvd erin ga chosen can improve understanding and cultural japan in a clear manner and detail, because Japanese culture learner look directly through access to a dvd. Besides, learner gained mastery vocabulary in japanese associated with a culture japan. After learning through cultural japan, learner also have confidence that rises to communicate by of the Japanese. Key word: Culture Japan, learning media